Imperfect loss offset and the after-tax expected rate of return to equity, with an application to rent taxation - Diderik Lund (University of Oslo, Department of Economics, 2000)
Non-neutral taxation, and in particular imperfect loss offset, is shown to have a strong effect not only on investment decisions, but also on required expected after-tax rates of return to equity. Systematic risk is valued according to the CAPM, while non-linear taxes are valued by option valuation methods.
Keywords: 330; Steuerbegünstigung; Verlust; Betriebswirtschaftliche Steuerlehre; Theorie